A model for arabidopsis thaliana cell suspension growth and sugar uptake kinetics - Mohamad Puad, Noor Illi; Abd-Karim, Khairiah; Mavituna, Ferda (2015)
In this study, a kinetic model was developed for batch growth and sugar consumption by the cell suspension cultures of Arabidopsis thaliana (A. thaliana) Columbia (Col) ecotype cultivated in the continuous dark condition. The model included sucrose hydrolysis by the cell-wall invertase enzyme into glucose and fructose and consumption of these hexoses at different rates to support cell growth. Several assumptions were made in order to simplify modelling of a complex system. The whole living cells in the culture were treated as one uniform biomass by assuming that all individual living cells are of the same size, shape, mass, age and physiology. In addition, temperature and all concentrations in the system were considered as uniform. All kinetic model parameters were obtained from a control experiment where Col cells were grown on 30 gL-1 sucrose as well as other independent experiments where Col cells were supplied with different concentrations and combinations of sugars. The model adequately described and predicted the growth and sugars profile of A. thaliana cells.